Social Work in Education: In times of work mediated from the perspective of digital technologies (Research, Society and Development, 2025)
Digital Information and Communication Technologies (ICTs) are present in a wide range of social spheres, including educational institutions. However, due to the changes in the Digital Age, they are increasingly being reshaped, with new approaches that require changes in the professional work practices of social workers. Objective: Understand in literature the use of ICTs as tools for mediating and interacting with socio-educational skills. Methodology: Documentary research of indirect sources for an Integrative Literature Review (ILR) was carried out through the descriptive method with a qualitative approach in journal research. CAPES Journal Portal database, the Sucupira Platform, the Scientific Electronic Library Online (SciELO), and public platforms. Result: The data were obtained from 20 (twenty) publications, corresponding to the years 2019 to 2025. Final considerations: The integration of these technologies not only facilitates mediation and interaction between social workers, students, and their families, but also transforms the traditional space-time relationship, enabling more agile and collaborative services. In this regard, the use of ICTs requires social workers to develop adaptive skills, capable of keeping up with the rapid digital and social changes present in contemporary times.